Effect of Silica Fume on Permeability and Microstructure of High Strength Concrete - Satish Kumar Chaudhary; Ajay Kumar Sinha (Civil Engineering Journal, 2020)
The important concrete structure in the vicinity of industry, thermal power plant suffers deterioration by the acid rain cause due to combination of CO2, SOx and NOx with rain water. A combined attack that is from acid as well as sulphate can be observed under impact of sulphuric acid. It attacks on Calcium hydroxide and form Calcium sulphate, which can be leached out easily and make Interfacial Transition Zone (ITZ) poor. The water retaining structure such as dam, weir should be impermeable and that can be achieved by binary cementitious blends, using Silica fume (SF). Silica fume a by product of silicon industry, proves very effective in improving the microstructure of concrete due to their finer particle size, approximately 100 times finer than cement particles. The SEM image of binary blended high strength concrete (HSC) with Silica fume shows the condensed packing of cement hydration product and a dense microstructure as compare to control mix. The water permeability test result reveals that there is about 87 percent reduction in the coefficient of permeability achieved by inclusion of 10% Silica fume (SF) by weight of cement. Rapid chloride penetration test (RCPT) has been performed to investigate the ingress of chloride ions into the concrete. There was significant reduction in chloride ions penetration recorded due to SF inclusion.